Percutaneous microwave coagulation therapy for hepatocellular carcinoma: Evaluation of irradiated region with dynamic CT - Kumazawa, Hiroaki; Maru, Yasushi; Yoshino, Masahiro; Onaya, Hiroaki; Sekiguchi, Ryuzou; Furuse, Junji; Miyamoto, Shin-ichi; Sumi, Hajime (Journal of Microwave Surgery, 1999)
We evaluated the size of irradiated regions after percutaneous microwave coagulation therapy (PMCT) to determine the optimal irradiation time in proportion to the tumor size in hepatocellular carcinoma (HCC). We reviewed the findings on dynamic CT within 5 days and one month after PMCT for 23 lesions in 20 patients with HCC. The tumor area was irradiated with microwaves for 2 to 9 minutes according to the tumor size. There was correlation between the size of hypoattenuation area after the treatment and irradiation time. Hyperattenuation surrounding the hypoattenuation area was frequently observed within 5 days after PMCT and made it difficult to evaluate the anti-tumor effect exactly. The finding almost disappeared one month after PMCT and we should evaluate the effect of treatment with dynamic CT in both periods.